Green Packaging as a Driver Of Sustainability - Aristote Marebuza Kadima (Uganda Christian University, 2023)
This study aimed to investigate the use of 'green packaging as a driver of sustainability.' The study had three major objectives, to investigate why there was a need for businesses and consumers to adopt green packaging, to investigate the type of packaging materials that were currently used and their environmental impact, to investigate the barriers and potential solutions to adopting green packaging by businesses and consumers. The study was purely descriptive and analytical, based on both qualitative and quantitative data from both primary and secondary sources. The data was collected using questionnaires and interviews during the data collection. A sample size of 55 respondents who are consumers and business owner are also used in the study. It was discovered that green packaging helped in reducing waste generation in businesses and consumers' operations, reduced costs, helped minimize greenhouse gas emissions, and gave a competitive advantage to businesses. It was found that single-use plastic and disposable plastic packaging significantly contributed to environmental waste. The use of paper and cardboard packaging was seen as related to deforestation and habitat destruction, though it had lower gas emissions and degradation impacts. Glass packaging's recyclability was recognized, while metal packaging was appreciated for its durability and recyclability. However, awareness about biodegradable and compostable packaging was low, and lastly, the most used packaging material was plastic, followed by paper and cardboard packaging material. It was also discovered that the cost and limited availability of green packaging materials were identified as barriers to the adoption of green packaging, along with consumer unawareness about the environmental impacts of traditional packaging. Inadequate regulations were also noted as a challenge in the implementation of green packaging practices. The study, therefore, concluded that green packaging is a driver of sustainability. The study further made recommendations for improvements and implementation of green packaging and drive to sustainability which where the raising of awareness about sustainability, reinforcement of regulation, give incentive to companies and organizations that implement green packaging in their activities but also penalties to those who do not comply with the regulation, government to support research and innovation in the packaging industry.
This is a dissertation.